Internalization of Recombinant Imiglucerase into Mouse Peritoneal Macrophages and L929 Mouse Fibroblasts - I. V. Lyagoskin; M. S. Pantyushenko; O. M. Strizhakova; N. K. Kudina; E. Yu. Prudnikova; P. V. Chichkanova; S. G. Abbasova (Биопрепараты: Профилактика, диагностика, лечение, 2020)
Enzyme replacement therapy (ERT) is one of the most efficient treatments for lysosomal storage diseases. Type 1 Gaucher disease is caused by β-glucocerebrosidase enzyme deficiency, which may be compensated for by intravenous infusions of imiglucerase—a recombinant enzyme. Imiglucerase targets macrophages and enters these cells via interaction with mannose receptors on the cell membrane. Characterisation of internalization of enzymes by target cells is important in the context of the development of new medicines and production of existing ERT medicines. The peritoneal and alveolar macrophages, as well as macrophages of the spleen of small laboratory animals (rats and mice) are widely used in such studies. However, isolation of cells from animal sources raises ethical issues, and therefore continuous mammalian cell lines may offer an attractive alternative. The aim of the study: to conduct comparative studies on the internalization of recombinant imiglucerase into mouse peritoneal macrophages and L929 mouse fibroblasts. Materials and methods: CerezymeR batches 7HV0913, C6214H05, 7HV0888 (Genzyme Ltd., UK); Glurazim batches 020416, 011117, 021117 (LLC “IBC “Generium”, Russia). We used peritoneal macrophages obtained from BALB/c mice and L929 mouse fibroblasts. The cells were cultured in DMEM/F12 complete growth medium with 10% fetal bovine serum. The activity of imiglucerase internalized into the cells was evaluated spectrophotometrically by hydrolysis of the artificial substrate—4-methylumbelliferyl-β-Dglucopyranoside. Results: the study compared internalization of recombinant imiglucerase (the active ingredient of CerezymeR and Glurazim) by mouse peritoneal macrophages and L929 mouse fibroblasts. It was demonstrated that the medicines activity in the lysates of peritoneal macrophages is comparable with that in the lysates of L929 mouse fibroblasts. Regardless of the model system, the activity of Glurazim stayed within the acceptable range (80–125%) established for biosimilar products. Conclusions: the experiments proved that L929 mouse fibroblasts could be recommended for assessment of internalization of recombinant imiglucerase.